Pembaharuan Hukum : Reformasi Sistem Peradilan Militer di Indonesia - Irman Putra; Arief Fahmi Lubis (Universitas 17 Agustus 1945 Semarang, 2020)
Reform of the military justice system (criminal law enforcement) is essentially part of the idea of law reform. Legal reform includes not only